Godless Minds: Exploring The Rise and Influence of New Atheist Thinkers - Mohamad Fuad, Mohamad Razif; Che Nordin, Khairul Naim; Hamat, Mohd. Fauzi; Qatawneh, Mohammad Abdelhamid Salem (Jurnal Usuluddin, 2023)
This study provides a concise history of New Atheism, highlighting its departure from traditional atheistic perspectives. The study identifies five defining features of New Atheism after exploring into the subtle differences. These include its recent emergence and widespread media coverage, the adoption of an outspokenly critical stance towards religion, the promotion of scientism and rationalism as intellectual pillars, and the advocacy for secularism in societal frameworks. Furthermore, the study unfolds with an in-depth examination of the movement's key figures, commonly known as "The Four Horsemen" - Sam Harris, Daniel Dennett, Christopher Hitchens, and Richard Dawkins. This study aims to improve the clarity of the ideological roots of New Atheism and its impact on contemporary debates about faith, reason, and secularism by examining their individual contributions.